A indústria 4.0: um estudo bibliográfico dos TCC´s apresentados ao curso ECAT- IFAM -CMDI no período de 2018 a julho 2022 - Oliveira, Rágison da Costa (Brasil, 2023)
The world is going through countless changes and paradigms, Industry 4.0 is a revolution that will impact both the industrial and the social environment, in the academic environment, academic productions that address this theme have already begun. It brings with it one of the interactions ever seen and is based on some technologies such as: Internet of Things, Additive Manufacturing, Test Beds, Big Data Analytics and Artificial Intelligence. This work seeks to present to the academy how these subjects are being approached by the academics of the Control and Automation Engineering course of IFAM-CMDI in their final works. The results showed that the authors use tools that are pillars of industry 4.0, although some do not address all the aspects that compose it in the course of the works studied.